Livestock development in the peasant sector of highland Ethiopia: Some policy issues and implications - Assefa, T. (International Livestock Centre for Africa, 1990)
Generally discusses policy and institutional issues related to the topic in post-revolution Ethiopia. The first part of the paper summarizes the physical resource base and the farming systems of the central highlands. Part two highlights the performance of the livestock sector and provides a very brief picture of the institutions involved in livestock development in these institutions with particular reference to the dairy sector. The third part surveys livestock investments made available by government, non-government organizations and formal credit institutions. The strategic policy issues in livestock development in the peasant sector are discussed in the fourth part. Part five explores the future prospects and the options available for developing the sector. Finally the paper presents the conclusions and policy implications.